Dairy Intake and Parkinson's Disease: A Mendelian Randomization Study. Issue 4 (8th January 2022) - Domenighetti, Cloé; Sugier, Pierre‐Emmanuel; Ashok Kumar Sreelatha, Ashwin; Schulte, Claudia; Grover, Sandeep; Mohamed, Océane; Portugal, Berta; May, Patrick; Bobbili, Dheeraj R.; Radivojkov‐Blagojevic, Milena; Lichtner, Peter; Singleton, Andrew B.; et al.
Abstract: Background: Previous prospective studies highlighted dairy intake as a risk factor for Parkinson's disease (PD), particularly in men. It is unclear whether this association is causal or explained by reverse causation or confounding. Objective: The aim is to examine the association between genetically predicted dairy intake and PD using two‐sample Mendelian randomization (MR). Methods: We genotyped a well‐established instrumental variable for dairy intake located in the lactase gene (rs4988235) within the Courage‐PD consortium (23 studies; 9823 patients and 8376 controls of European ancestry). Results: Based on a dominant model, there was an association between genetic predisposition toward higher dairy intake and PD (odds ratio [OR] per one serving per day = 1.70, 95% confidence interval = 1.12–2.60, P  = 0.013) that was restricted to men (OR = 2.50 [1.37–4.56], P  = 0.003; P ‐difference with women = 0.029). Conclusions: Using MR, our findings provide further support for a causal relationship between dairy intake and higher PD risk, not biased by confounding or reverse causation. Further studies are needed to elucidate the underlying mechanisms. © 2022 International Parkinson and Movement Disorder Society